Regulatory pressure and income smoothing by banks in response to anticipated changes to the Basel II Accord - Chu Yeong Lim; Kevin Ow Yong (China Journal of Accounting Research, 2017)
We examine the effects of the revised Basel II rules on bank managers' discretionary behavior, specifically income smoothing and loan loss provisioning. As the revised rules exert greater regulatory pressure on corporate than retail banking, we predict corporate bank managers to reduce risk-taking activities or increase income smoothing. Analysis of segmental reports reveals greater (less) income smoothing in the corporate banking segments of low-capital (high-capital) banks during the Basel II period, with their managers recognizing loan loss provisions in a less timely fashion. We find no such effects for retail banking. Although we document an initially negative market reaction to the regulatory announcements, that reaction weakens over time. Overall, the study highlights the unintended consequences of the banking rule changes.
Keywords: M41; M48; 650; Basel Accord; Income smoothing; Loan loss provisions; Corporate banking; Retail banking